Thanksgiving and Christmas gatherings before the 2020–21 winter surge of COVID-19 in the United States - Tim A. Bruckner; Abhery Das; Greg J. Duncan (Preventive Medicine Reports, 2022)
Objective: COVID-19 in the US disproportionately affected, and continues to affect, racial/ethnic minorities. Although risky social gatherings for Thanksgiving and Christmas in 2020 contributed substantially to the “winter surge” in cases and deaths, no research examines potential racial/ethnic differences in behaviors related to holiday gatherings. Design: We used the Understanding America Survey (UAS) - Coronavirus Tracking, a nationally representative study of US adults, to examine associations between race/ethnicity and risky holiday gathering behavior (i.e., gathering with non-household members and with little to no social distancing or mask-wearing). We applied logistic regression models to examine racial/ethnic and socioeconomic differences in risky holiday gatherings while accounting for a person’s pre-holiday perception of COVID-19 risk as well as related behaviors. Results: Non-Hispanic Black adults showed a lower prevalence of attending a risky Thanksgiving gathering than did non-Hispanic White adults (15 % vs 43 %, p <.001). The magnitude of this racial/ethnic difference was also found for risky Christmas gatherings. Hispanic and “Other” race/ethnicity adults also appeared less likely than non-Hispanic whites to attend a risky holiday gathering. Higher-income households attended a risky holiday gathering more frequently, when compared with lower income households (p <.001). Logistic regression results, which controlled for other COVID-19 related behaviors, support these main findings. Conclusions: Racial/ethnic minorities, and non-Hispanic Black adults in particular, appeared least likely to have engaged in risky holiday gatherings in late 2020. If replicated, our findings appear consistent with the notion that behavioral modification among racial/ethnic minorities may have reduced the intensity of the 2020/21 “winter surge” in COVID-19.